(untitled) (SOUTH ARAL SEA MEDICAL JOURNAL, 2025)
Insufficient physical activity negatively affects the functioning of the pancreas and its ability to maintain normal enzyme levels. A decrease in physical activity causes a reduction in the production of the most important pancreatic enzymes - amylase, lipase and proteases, which are responsible for the breakdown of carbohydrates, fats and proteins. This may result in difficulties with digestion, impaired absorption of nutrients and other dyspeptic disorders.